Forma, valor e renda na arquitetura contemporânea (ARS, 2010)
Contemporary architecture is dangerously enmeshed with the entertainment industry and the field of advertising. This meshing has pushed architectural form to the limits of materiality. Architecture today searches for maximum informational rent, a process typical of global product branding; through this process, established building and production principles are subverted by a play of volumes and effects beyond any rule or limitation. Relying on digital design technologies and the reorganization of the building site, this new fetishism of form, analogous to the autonomization of power and abstract wealth in contemporary capitalism, defines the new condition of cutting-edge architecture.